2019
DOI: 10.35940/ijitee.k2120.0981119
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Justice and Turnover Intention: The Mediating Role of Quality of Working Life

Abstract: Turnover intention (TI) is one of the critical issues that confront organizations and cost high capital investment. Most of previous studies focus on this issue among business organization while few examined it in public sector. Accordingly, this paper aims to examine the effect of organizational justice (OJ) on turnover intention among police personnel in United Arab Emirates (UAE). Further, quality of working life (QWL) is examined as a mediator between OJ and TI. A quantitative approach was deployed using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Te study conducted by Gillet et al [31] revealed that transformational leadership directly afects the quality of work life for nurses and this efect is mediated by justice. In a study, Kasim and Aldarmaki [45] investigated the connection between justice, quality of work life, and turnover intention among police personnel in the United Arab Emirates. Teir fndings suggested that the quality of work life acts as a mediator in the relationship between justice and turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Te study conducted by Gillet et al [31] revealed that transformational leadership directly afects the quality of work life for nurses and this efect is mediated by justice. In a study, Kasim and Aldarmaki [45] investigated the connection between justice, quality of work life, and turnover intention among police personnel in the United Arab Emirates. Teir fndings suggested that the quality of work life acts as a mediator in the relationship between justice and turnover intention.…”
Section: Discussionmentioning
confidence: 99%